Macular vessel density, branching complexity and foveal avascular zone size in normal tension glaucoma - Cheng, Kelvin K. W.; Tan, Beatrice L.; Brown, Lyndsay; Gray, Calum; Bianchi, Eleonora; Dhillon, Baljean; MacGillivray, Tom; Tatham, Andrew J. (Scientific reports, 2021)
The aim of this study was to investigate the relationship between glaucoma severity and perifoveal vessel density (pfVD), branching complexity, and foveal avascular zone (FAZ) size in normal tension glaucoma (NTG). 31 patients with NTG washed out of glaucoma medications were subjected to tests including; intraocular pressure measurement; standard automated perimetry; optical coherence tomography (OCT) measurement of macular ganglion cell complex (mGCC), inner macular thickness (IMT) and circumpapillary retinal nerve fibre layer (cpRNFL); and OCT angiography measurement of pfVD, FAZ perimeter and multispectral fractal dimensions (MSFD). Eyes with more severe glaucoma had significantly thinner mGCC and cpRNFL and lower pfVD. MD decreased by 0.4 dB (95% CI 0.1 to 0.6 dB, P = 0.007) for every 1% decrease in pfVD. Lower MSFD was observed in eyes with lower pfVD and in patients with systemic hypertension. Multivariable analysis, accounting for age and OCTA quality, found lower pfVD remained significantly associated with thinner IMT, thinner mGCC and worse MD but not with MSFD. pfVD was reduced in NTG and was diminished in eyes with worse MD. Macular vessel branching complexity was not related to severity of visual field loss but was lower in patients with systemic hypertension.